Embedded medical sensors, an emerging technology to monitor hearts, brains, nerves and addressing other medical applications for improved patient care. Issue 2 (21st March 2016) - Bloss, Richard
Abstract : Purpose: The purpose of this paper is to review the dramatic entry of embedded medical sensors into the medical monitoring environment. It also examines the current range of applications that have been addressed, trends for additional applications and factors driving this movement. Design/methodology/approach: This paper is a review of published information and papers on research as well as contact and discussions with researchers in this field at universities, manufacturers and research centers. Findings: Microelectronics and electrochemical technologies have been a major factor in this development along with technology advancements to transmit energy and signals to and from miniature electronic devices, thus eliminating the need for stored energy and wires for transmitting information. Sensors are addressing medical issues in the heart, the brain, cancer treatment and prosthetic control. The move to implanted sensors follows development of other implanted medical devices as well as wearable sensors. Originality/value: Readers may be very excited to learn of the many new tasks that embedded medical sensors can address and the many unique benefits that are provided to the patient and the medical staff caring for the patient.